Hydrogenation and dehydrogenation of nitrogen-doped graphene investigated by X-ray photoelectron spectroscopy - Späth, Florian; Zhao, Wei; Gleichweit, Christoph; Gotterbarm, K.; Bauer, Udo; Höfert, Oliver; Steinrück, Hans-Peter; Papp, Christian (Surface Science, 2015)
We studied the hydrogenation and dehydrogenation of nitrogen-doped graphene (NDG) by in situ high-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS (TPXPS). Nitrogen-doped graphene was prepared by low energy nitrogen implantation in pristine graphene on Ni(111). Hydrogenation of NDG was performed by exposure to atomic hydrogen. Upon hydrogenation the XP spectra in the C 1s region reveal one new peak, shifted to lower binding energies as compared to graphene, which is associated with newly formed CH groups. In the N 1s region two ne wpeaks, shifted to higher binding energies are observed; these are associated with hydrogenated pyridinic and graphitic nitrogen. TPXPS spectra reveal a different thermal stability of the two hydrogenated nitrogen species,while the C–H groups of graphene show no significant changes compared to undoped hydrogenated graphene.